THE ROLE OF MOTOR SKILLS IN IMPROVING TECHNIQUES IN YURCENKO JUMP (GYMNASIUM, 2017)
I approach this work from the point of view of the importance given to the accurate learning  of this jump, which further offers the possibility of succeding in some other high difficulty jumps. For learning and improving the jumps through Yurchenko in the artistic gymnastics, the development of the following movement qualities is necesary: strength, speed, mobility and skill fulness, which are specific to the jumps through rondat flick-flack testing, and the means used in our experinment have an important contribution in the significant increasing of the strengh indicators, speed indicator and scapulo-humeral mobility, after which a progress or 0,62 points in the technical execution of the jump has been registered, compared to the initial testing of the experimental group, and 0,48 points compared to the withness group, during the 4 months of training.